Studies on Adsorptive Behavior of Cd2+ on Graphene Oxide: Alternative Novel Approach - A. U. Nkwoada; C. O. Alisa; C. K. Enenebeaku; E. E. Oguzie (Archives of Current Research International, 2018)
Certain adsorptive mechanisms and interactions often exist within linearized kinetic functions which are largely unreported. A novel inverse saturation modeling was applied to evaluate the adsorptive behavior of super-saturation, saturation, and desorptive processes on linear kinetic function plots using pseudo 1st order, pseudo 2nd order, Elovich and Intra-particle diffusion. Graphene oxide was prepared by room temperature synthesis and used as adsorbent over Cd2+ adsorbate. Batch adsorption process was conducted and four error functions were utilized. The sum of squares of the errors and Sum of absolute errors identified pseudo 2nd order as having the least deviation at 0.113 and 0.337 respectively. The modelled pseudo 1st order reaction had R2 = 0.985 while the inverse saturation model had R2 value of 0.998, both been a better data fit than non-modelled pseudo 1st order R2 at 0.917. The slower reaction kinetics in pseudo 1st order was due to super-saturation during adsorption as shown by inverse saturation point. The correlation coefficient of modeled kinetic plot of pseudo 2nd order, Intra particle diffusion and Elovich had R2 = 1. The Elovich inverse saturation plot showed that the graph was an L-isotherm type indicating progressive saturation. The rate determining step experienced by Intra-particle diffusion was accommodated by wide range of inverse saturation plots showing adsorption, supersaturation and desorption as points of greatest influence. The inverse saturation plot of pseudo 2nd order plot had absolute slope of 2.656 and large intercept of 24.815 driving it’s faster reaction kinetics. Hence, the inverse saturation point modelling provided a much better interpretation of adsorptive behavior of graphene oxide adsorbent over Cd2+ adsorbate.